A REPORT ON THE EXISTENCE OF HERITIERA LITTORALIS DRYAND. ON THE COAST OF MAHARASHTRA - S. S. SHAIKH,; M. V. GOKHALE,; N. S. CHAVAN, (The Bioscan, 2011)
Heritiera littoralis Dryand is a new addition to the mangrove flora of Maharashtra. This is a rare-most and narrowly distributed species along the coastline of this state. Very few individuals are located and the species demands immediate conservation measures. As a part of its conservation biology, the present work throws the light on its morpho-taxonomy, phenology, seedling morphology, habitat and regeneration.